Time to let go of CARP? Not so fast - Toby C. Monsod; Sharon A. Piza (University of the Philippines, School of Economics (UPSE), 2014)
The following note seeks to clarify the appreciation of data pertaining to agrarian reform as used in the discussion paper "CARP: time to let go" (henceforth Fabella (2014)). Fabella (2014) has three parts: the first part argues that "the cumulative weight of evidence suggests that the hypothesis that in economic terms CARP is a government failure has not been rejected." The second part offers possible reasons for that failure. The third part concludes, saying it is time to let go.
Keywords: 330; CARP